PAPAL MAGISTERIUM AND SENSUS FIDELIUM: EXAMING THE CASE FOR THE PRIESTLY ORDINATION OF WOMEN - Kirchberger, Georg (Asian Horizons, 2018)
Using the teaching of Vatican II regarding sensus fidei as his starting point, the author uses discussion in the Catholic Church regarding the ordination of women as an example of the fact that papal magisterium in the Catholic Church still often overlooks that sensus fidei. Firstly, the author describes the often repeated claim by the teaching authority of the Catholic Church that women cannot be ordained priests and participate in the leadership of the Church. He then puts forward the argument promulgated by the papal magisterium, followed by difficulties related to it, and criticism of it. Finally, he presents four basic dogmatic principles which support the opinion that women have the spiritual qualifications to be ordained to the priesthood, and in doing so be signs of the presence in the assembly of Christ as head of the Church.